2016
DOI: 10.1002/ange.201511917
|View full text |Cite
|
Sign up to set email alerts
|

Homolytic Cleavage of a B−B Bond by the Cooperative Catalysis of Two Lewis Bases: Computational Design and Experimental Verification

Abstract: Density functional theory (DFT) investigations revealed that 4-cyanopyridine was capable of homolytically cleaving the BÀB s bond of diborane via the cooperative coordination to the two boron atoms of the diborane to generate pyridine boryl radicals.Our experimental verification provides supportive evidence for this new B À Ba ctivation mode.Witht his novel activation strategy,wehave experimentally realized the catalytic reduction of azo-compounds to hydrazine derivatives,d eoxygenation of sulfoxides to sulfid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…During our investigations, we found that 2 can undergo hydrolysis upon stirring in degassed deionized H 2 O overnight, affording the corresponding 1,2‐diphenylhydrazine ( 13 , Scheme , a ). This result, albeit accessed through palladium catalysis, supports the proposed mechanism by Li and co‐workers, whereby 2 was computationally calculated as an intermediate in the organocatalytic formation of hydrazines from their corresponding azobenzenes . Interestingly, theirreaction conditions proved to be ineffective for the hydrolysis of 9 .…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…During our investigations, we found that 2 can undergo hydrolysis upon stirring in degassed deionized H 2 O overnight, affording the corresponding 1,2‐diphenylhydrazine ( 13 , Scheme , a ). This result, albeit accessed through palladium catalysis, supports the proposed mechanism by Li and co‐workers, whereby 2 was computationally calculated as an intermediate in the organocatalytic formation of hydrazines from their corresponding azobenzenes . Interestingly, theirreaction conditions proved to be ineffective for the hydrolysis of 9 .…”
Section: Methodssupporting
confidence: 82%
“…These require the use of either an extremely reactive B–B bond in the form of azadiboriridenes, dichlorodiboranes, or a highly strained B–B bond as in [2]borametallarenophanes (Scheme ) . Recently, however, a combined computational and experimental article from Li and co‐workers showed that the diboration of N=N bonds using a commercially available and air‐stable tetraalkoxydiboron reagent such as bis(pinacolato)diboron is feasible . To the best of our knowledge there are no examples in the literature of N=N silaborations.…”
Section: Methodsmentioning
confidence: 99%
“…We were particularly interested in the use of organic diboron reagents because of their unique Lewis acidity and reducing ability ( vide supra ). Previous work in the area of synthetic organic chemistry showed that, upon binding to a Lewis basic oxygen atom, these organic diboron species can function as single electron reducing agents, thus allowing for various important transformations (Liu et al., 2019, Mo et al., 2010, Mo et al., 2018, Pietsch et al., 2015, Wang et al., 2016, Zhang and Jiao, 2017). Based on these reasons, we envisioned that, upon the coordination of such diboron compounds with the surface oxygen atom in metal oxide materials, the formation of surface diboron-oxygen Lewis pair may induce single electron transfer from the ipso -O 2c site to the adjacent Ti site.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, radical coupling of the aryl radical and boryl radical C produces the borylation product, along with the pyridine catalyst. Very recently, Li and co‐workers reported the application of a pyridine‐stabilized boryl radical to the catalytic reduction of azobenzene compounds and radical addition/carbon‐carbon coupling of α,β‐unsaturated ketones . Therefore, this in situ generated base‐stabilized boryl radical can be used as a bifunctional “reagent”, which acts not only as a boryl radical, but also as a pyridine precursor.…”
Section: Borylation Of Aryl (Pseudo)halidesmentioning
confidence: 99%